2005
DOI: 10.1111/j.1365-2109.2005.01353.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic certification of presumed hybrids of blue x red abalone (Haliotis fulgens Philippi and H. rufescens Swainson)

Abstract: Presumed hybrids between Haliotis rufescens and H. fulgens abalones, produced in a commercial abalone laboratory, were evaluated for progeny viability, gonad characteristics and for their 'true' status as hybrids by means of allozyme and microsatellite analyses. Four out of 10 evaluated allozyme loci proved to be useful for the genetic certi¢cation of hybrids, Gpi, Mdh-1, Mdh-2 and Sod, as they had exclusive alleles for each of the abalone reference species from which the presumed hybrids were produced. Three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 20 publications
(24 reference statements)
0
14
0
1
Order By: Relevance
“…Backcrossing between hybrid females and H. rufescens males was conducted to estimate progeny viability, resulting in significantly lower survival rates for trochophores and postlarvae than those observed from non-hybrid females. The survival rate of hybrid trochophore larvae (20 h old) was 4.5%, whereas the survival rate of late veliger larvae (120 h old) was only 2.9%, which was significantly lower compared with the 62.2 and 70.4% registered in progeny from pure crosses of H. rufescens (Hernández- Ibarra et al 2005).…”
Section: Californian Experiencesmentioning
confidence: 76%
See 1 more Smart Citation
“…Backcrossing between hybrid females and H. rufescens males was conducted to estimate progeny viability, resulting in significantly lower survival rates for trochophores and postlarvae than those observed from non-hybrid females. The survival rate of hybrid trochophore larvae (20 h old) was 4.5%, whereas the survival rate of late veliger larvae (120 h old) was only 2.9%, which was significantly lower compared with the 62.2 and 70.4% registered in progeny from pure crosses of H. rufescens (Hernández- Ibarra et al 2005).…”
Section: Californian Experiencesmentioning
confidence: 76%
“…Interestingly, phylogenetic relationships among California species suggested by haemocyanin affinity analyses (Meyer 1967), protein electrophoresis (Brown 1993), sperm lysin DNA sequences (Lee & Vacquier 1992;Lee et al 1995), DNA egg receptor protein sequence vitelline envelope receptor for lysin gene (VERL) , Interval Transcribed Sequence (Coleman & Vacquier 2002) and haemocyanin sequences (Streit et al 2006) show close relationships (genetic proximity) between these species. More recent studies by Ibarra et al (2005) have produced and confirmed hybrids between H. rufescens $ and H. fulgens # on Mexico's commercial abalone farms, and have analysed the gametes of hybrid adult abalone (4-4.5 years old). The results show normal ovogenesis in hybrid females, whereas hybrid males show abnormal spermatogenesis and partial sterility.…”
Section: Californian Experiencesmentioning
confidence: 99%
“…Previous studies using allozymes indeed described the genetic difference between the hybrids and their parental species (Brown and Murray, 1992;Hoshikawa et al, 1998;Ibarra et al, 2005;Ahmed et al, 2008). However, the use of allozyme loci failed to provide a sufficient genetic basis of hybrids, probably due to the less informative nature of allozyme loci.…”
Section: Discussionmentioning
confidence: 99%
“…Hibridisasi interspesifik selain dihadapkan pada kendala asinkronisasi pemijahan, juga ketidaksamaan daya tetas (Lafarga-De la Cruz et al, 2012), dan viabilitas yang lebih rendah (Ibarra et al, 2005). Seperti yang telah dijelaskan sebelumnya, pada penelitian ini terjadi pula kendala asinkronisasi pemijahan, selain itu terjadi abnormalitas pada perkembangan embrionya.…”
Section: Daya Tetas Telurunclassified